What is the Real Rate of Radial Nerve Injury After Humeral Nonunion Surgery?. Issue 8 (August 2020) - Koh, Justin; Tornetta, Paul; Walker, Brock; Jones, Clifford; Sharmaa, Tayseer; Sems, Stephen; Ringenbach, Kathleen; Boateng, Henry; Bellevue, Kate; Firoozabadi, Reza; Spitler, Clay; Saxena, Sharul; et al.
Abstract : Objectives: To determine the radial nerve palsy (RNP) rate and predictors of injury after humeral nonunion repair in a large multicenter sample. Design: Consecutive retrospective cohort review. Setting: Eighteen academic orthopedic trauma centers. Patients/Participants: Three hundred seventy-nine adult patients who underwent humeral shaft nonunion repair. Exclusion criteria were pathologic fracture and complete motor RNP before nonunion surgery. Intervention: Humeral shaft nonunion repair and assessment of postoperative radial nerve function. Main Outcome: Measurements: Demographics, nonunion characteristics, preoperative and postoperative radial nerve function and recovery. Results: Twenty-six (6.9%) of 379 patients (151 M, 228 F, ages 18–93 years) had worse radial nerve function after nonunion repair. This did not differ by surgical approach. Only location in the middle third of the humerus correlated with RNP ( P = 0.02). A total of 15.8% of patients with iatrogenic nerve injury followed for a minimum of 12 months did not resolve. For those who recovered, resolution averaged 5.4 months. On average, partial/complete palsies resolved at 2.6 and 6.5 months, respectively. Sixty-one percent (20/33) of patients who presented with nerve injury before their nonunion surgery resolved. Conclusion: In a large series of patients treated operatively for humeral shaft nonunion, the RNP rate was 6.9%. Among patients with postoperative iatrogenic RNP, the rate of persistent RNP was 15.8%. This finding is more generalizable than previous reports. Midshaft fractures were associated with palsy, while surgical approach was not. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.